Etiopathogenesis and diagnosis of inflammatory odontogenic cysts: literature review (Research, Society and Development, 2020)
Odontogenic cysts are pathological cavities with epithelial lining and surrounded by fibrous connective tissue that originates from odontogenic tissues, they are classified as developmental and inflammatory cysts. The aim of this study was to conduct a literature review seeking information on the etiopathogenesis and diagnosis of apical and residual inflammatory odontogenic cysts, which frequently affect the maxillary bones. As a methodology, a narrative literature review was carried out, the population of this study consisted of articles indexed in the PubMed, SciELO and Google Scholar databases, in addition to books on oral pathology and stomatology. The descriptors used were: “Odontogenic Cysts”, "Oral Pathology" and "Dental Assistance". Root cysts develop as a result of inflammation at the root apex, caused by caries or trauma. The diagnostic methods used to identify root lesions are clinical, radiographic, histopathological examination and computed tomography. As a conclusion, it was observed that the specific etiological factors inducing periapical injuries are not fully known, thus requiring further studies to better understand these injuries, and currently, Cone-Beam Computed Tomography (CBCT) has been shown to be the best diagnostic method in cases that biopsy is not possible and for surgical planning.